Seismic assessment of ductile concentrically braced frames with HSS bracings - Faytarouni, Mahmoud; Şeker, Onur; Akbaş, Bülent; Shen, Jay (Elsevier Sci Ltd, 2019)
A study on the seismic ductility demands on square HSS braces in special concentrically braced frames (SCBFs) is presented to address the seismic risk of braces in existing SCBF buildings designed according to both previous and current AISC Seismic Provisions. First, the paper discusses the development of ductility-based fragility curves by employing specimens with various width-to-thickness and slenderness ratios collected from 16 experimental programs from 1978 to today. Second, the constructed fragility curves are used to estimate the vulnerability of square HSS braces to the damage state of fracture using the brace ductility demand as engineering demand parameter. Then, the seismic risk of braces in terms of fatigue life is evaluated under 30 earthquake ground motions using a seven-story office building designed following requirements of previous and current design practice. The study concludes that braces in SCBF designed in compliance with the previous and current AISC Seismic Provisions are subject to a high probability of fracture under earthquake ground motions characterized by different intensity levels, which in turn might lead to underestimation of the overall seismic risk.
Keywords: Square HSS braces; Concentrically braced frames; Width-to-thickness ratio; Probability of fracture; Ductility capacity; Fragility analysis; Seismic evaluation; Incremental dynamic analysis